Severe hypoglycaemia in type 1 diabetes mellitus: underlying drivers and potential strategies for successful prevention. Issue 3 (March 2014) - Little, S. A.; Leelarathna, L.; Barendse, S. M.; Walkinshaw, E.; Tan, H. K.; Lubina Solomon, A.; de, N.; Rogers, H.; Choudhary, P.; Amiel, S. A.; Heller, S. R.; Evans, M.; et al.
Summary Hypoglycaemia remains an over‐riding factor limiting optimal glycaemic control in type 1 diabetes. Severe hypoglycaemia is prevalent in almost half of those with long‐duration diabetes and is one of the most feared diabetes‐related complications. In this review, we present an overview of the increasing body of literature seeking to elucidate the underlying pathophysiology of severe hypoglycaemia and the limited evidence behind the strategies employed to prevent episodes. Drivers of severe hypoglycaemia including impaired counter‐regulation, hypoglycaemia‐associated autonomic failure, psychosocial and behavioural factors and neuroimaging correlates are discussed. Treatment strategies encompassing structured education, insulin analogue regimens, continuous subcutaneous insulin infusion pumps, continuous glucose sensing and beta‐cell replacement therapies have been employed, yet there is little randomized controlled trial evidence demonstrating effectiveness of new technologies in reducing severe hypoglycaemia. Optimally designed interventional trials evaluating these existing technologies and using modern methods of teaching patients flexible insulin use within structured education programmes with the specific goal of preventing severe hypoglycaemia are required. Individuals at high risk need to be monitored with meticulous collection of data on awareness, as well as frequency and severity of all hypoglycaemic episodes. Copyright © 2013 John Wiley & Sons, Ltd.